2016
DOI: 10.1177/0963662516656110
|View full text |Cite
|
Sign up to set email alerts
|

Public engagement in Malawi through a health-talk radio programme ‘Umoyo nkukambirana’: A mixed-methods evaluation

Abstract: Radio is an effective source of health information in many resource poor countries. In Malawi, 53% of households own radios however few radio programmes in Malawi focus on health issues in the context of medical research. An interactive health-talk radio programme ‘Umoyo nkukambirana’ was introduced by Malawi-Liverpool-Wellcome Trust Clinical Research Programme on a national radio station. The aim was to increase awareness of health and medical research, and improve engagement between researchers, healthcare w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Radio was the most common source of information on cervical cancer and screening followed by health workers. This finding is consistent with a study that was conducted by Nyirenda and colleagues [14] on public engagement in Malawi through a health-talk radio programme which found that men's participation from the rural area was greater than that of women. This might be attributed to the fact that many people in rural areas especially men rely on the radio for information on different development programmes [15].…”
Section: Sources Of Informationsupporting
confidence: 90%
See 2 more Smart Citations
“…Radio was the most common source of information on cervical cancer and screening followed by health workers. This finding is consistent with a study that was conducted by Nyirenda and colleagues [14] on public engagement in Malawi through a health-talk radio programme which found that men's participation from the rural area was greater than that of women. This might be attributed to the fact that many people in rural areas especially men rely on the radio for information on different development programmes [15].…”
Section: Sources Of Informationsupporting
confidence: 90%
“…Just a few of the participants" spouses have been screened for cervical cancer in this study. These results are similar with several studies that have found low utilization of cervical cancer screening services in Africa [12][13][14]. In rural, Zimbabwe Mupepi and colleagues [11] found that only 9 % of the study participants had been screened for cervical cancer.…”
Section: Knowledge About Cervical Cancer and Screeningsupporting
confidence: 89%
See 1 more Smart Citation
“…Many publications report use of community sensitization meetings, media, and involvement of community leaders, community representatives and other stakeholders to increase knowledge of medical research, improve study acceptability and support trial implementation, rather than engaging communities in participatory processes throughout research design and implementation 611 .…”
Section: Introductionmentioning
confidence: 99%
“…Other methods of dissemination such as theatre, which has been used to effect in this setting (Stuttaford et al 2006), postal drops of small, focused A5 pictograms, community radio, TV and social media may be useful in communicating results. Radio-based soap operas or talk shows (edutainment) have been effective in engaging the public with health research in Malawi (Nyirenda et al 2016) and South Africa (Jana et al 2015). Longitudinal HDSS sites have an opportunity to develop strategies for regular information sharing through community advisory groups (Reddy et al 2010) and wider village-based dissemination.…”
Section: Implications For Knowledge Dissemination Interventionsmentioning
confidence: 99%